Late Breaking Results From Hybrid Design Automation for Field-coupled Nanotechnologies - Hofmann, Simon; Walter, Marcel; Servadei, Lorenzo; Wille, Robert (2023 60th ACM/IEEE Design Automation Conference (DAC), 2023)
Recent breakthroughs in atomically precise manufacturing are paving the way for Field-coupled Nanocomputing (FCN) to become a real-world post-CMOS technology. This drives the need for efficient and scalable physical design automation methods. However, due to the problem's NP-completeness, existing solutions either generate designs of high quality, but are not scalable, or generate designs in negligible time but of poor quality. In an attempt to balance scalability and quality, we created and evaluated a hybrid approach that combines the best of established design methods and deep reinforcement learning. This paper summarizes the obtained results.